The selection of possible talents in the boxing sports in the Cayamo community - Prudencio Blanco-Durades; Andrés Fuentes-Domínguez (Universidad de Guantánamo, 2016)
The research proposes a system of actions to enhance the selection of potential talents in Boxing sporting the Cayamo community in Caimanera. The work provides a set of actions characterized essentially by the contribution in the practical order of procedures to enhance the selection of potential talents and boxers, who may face at early age their tasks more efficiently. From the review and updating of these tasks it was applied the criteria method of specialists, which confirmed the feasibility of the proposed system.